Relationship Between Fat-Soluble Vitamin Supplementation and Blood Concentrations in Adolescent and Adult Patients With Cystic Fibrosis. (August 2014) - Siwamogsatham, Oranan; Dong, Wei; Binongo, Jose N.; Chowdhury, Ritam; Alvarez, Jessica A.; Feinman, Shawna J.; Enders, Jessica; Tangpricha, Vin
Background : Pancreatic insufficiency is common in patients with cystic fibrosis (CF) and leads to malabsorption of fat-soluble vitamins. Multivitamins, including vitamins A, D, E, and K, are routinely prescribed to patients with CF to prevent vitamin deficiencies. Our objective was to examine the relationship between fat-soluble vitamin supplements and their impact on blood concentrations. Methods : This was a retrospective chart review of patients with CF who were treated at Emory Clinic and Emory University Hospital during 2008–2012. The amount of fat-soluble vitamin supplementation, serum markers of fat-soluble vitamin concentrations, CF transmembrane conductance regulator genotype, and other demographic information were recorded from electronic medical records. Mixed-effects models were used to investigate the trends over time of fat-soluble vitamin supplements and serum vitamin concentrations. Results : In total, 177 charts were eligible. Mean (SD) age was 26.1 (10.2) years. Ninety-two percent of patients had pancreatic insufficiency and 52% had the homozygous ΔF508 mutation. Recorded fat-soluble vitamin supplementation increased in the past 5 years ( P < .001 for all). Serum 25-hydroxyvitamin D increased slightly (3% increase; P < .01); however, there were no changes in the blood concentrations of vitamins A, E, and K ( P = .26–.96). Conclusions : Despite a near doubling of recorded fat-soluble vitamin supplementation over the past 5 years, there was no parallel increase in blood concentrations of these vitamins. Potential reasons include suboptimal dosages, low adherence, or ongoing issues with malabsorption.